1995
DOI: 10.1001/archsurg.1995.01430020067011
|View full text |Cite
|
Sign up to set email alerts
|

Free Perforation of Gastric Carcinoma

Abstract: A significant proportion of patients can be saved and offered good palliation with emergency gastrectomy; those likely to die can be identified before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 6 publications
4
62
0
4
Order By: Relevance
“…Of those, nine articles were included in this qualitative review of perforated gastric cancer (Table 1) [3][4][5][6][7][8][9][10][11]. Two of the articles report outcomes on the same series of patients; therefore, results are reported together to avoid duplication [6,7].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of those, nine articles were included in this qualitative review of perforated gastric cancer (Table 1) [3][4][5][6][7][8][9][10][11]. Two of the articles report outcomes on the same series of patients; therefore, results are reported together to avoid duplication [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…In 8 of the 9 studies, a preoperative diagnostic status was reported by the authors. On average, fewer than half of the patients presenting with perforation and receiving subsequent treatment had a preoperative or intra-operative diagnosis of gastric cancer [3][4][5][6][7][9][10][11]. Jwo et al [9] reported one patient who experienced perforation during chemotherapy for metastatic disease.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations